Knowlwdge of pregnant women attended in prenatal care services regarding the anti HIV test - Suely Deysny de Matos; Rosilene Santos Baptista; Inacia Sátiro Xavier de França; Fabíola de Araújo Leite Medeiros; Virgínia Rossana de Sousa Brito (Rev Rene)
This is a descriptive study conducted from 2005 to 2006 which aimed to investigate the pregnant women knowledge concerning HIV test and to identify the main reasons that motivate these women not to take the examination. It was conducted an interview with 62 pregnant women registered in five Family Health Basic Units of the – FHBU. The content analysis allowed the identification of thematic groups: pregnant women knowledge of AIDS and disinformation of them concerning AIDS and its ways of transmission. The women have poor socioeconomic condition; they do not understand well the meaning of anti-HIV, or its significance in prenatal care. Most of the pregnant women did not accept to do that test either because they were not asked to do so or because they were not informed about it. There is need for permanent implementation of health education on prevention and transmission of HIV and training of health professionals to advise pregnant women seeking for greater adhesion to the anti-HIV test.